Understanding Hezbollah symbolism through symbolic convergence theory. Issue 1 (1st June 2021) - Matusitz, Jonathan
This article applies symbolic convergence theory (SCT) to the type of symbolism used by Hezbollah, a Shia terrorist organization. By and large, SCT posits that sharing group fantasies contributes to symbolic convergence. The success of symbolic convergence hinges on three important concepts: symbolic cue, fantasy type and saga. An example of a symbolic cue is Hezbollah's yellow-and-green logo that symbolizes global militancy against infidels. In regards to the organization's fantasy types, eight of them were identified (e.g. Al-Quds Day, definition of enemies and individual self-sacrifice). Apropos of Hezbollah's sagas, two figureheads, Ruhollah Khomeini (the Grand Ayatollah in Iran) and Hassan Nasrallah (the current Hezbollah leader), have become idols of worship by hundreds of thousands of Hezbollah members and millions of Shia Muslims. An important conclusion is that events can be more important for their symbolism than their very happening or existence. Hence, through symbolism, Hezbollah can strike a chord within its followers so as to produce significant change in the world.